Cover Image. Issue 3 (28th January 2021) - Bargagna‐Mohan, Paola; Schultz, Gwendolyn; Rheaume, Bruce; Trakhtenberg, Ephraim F.; Robson, Paul; Pal‐Ghosh, Sonali; Stepp, Mary Ann; Given, Katherine S.; Macklin, Wendy B.; Mohan, Royce
Abstract : Nonmyelinating corneal Schwann cells ensheathing axons in the corneal stroma were visualized by the expression of green fluorescent protein under the control of the proteolipid protein 1 gene promoter in transgenic mice. This en face three‐dimensional image reconstruction of z‐stacks obtained by confocal microscopic imaging of whole mount corneas shows the elaborate branching of corneal axons. The nuclei of corneal epithelial cells was revealed by counter staining with a blue‐colored nuclear dye. The cover image is based on the Research Article Corneal nonmyelinating Schwann cells illuminated by single‐cell transcriptomics and visualized by protein biomarkers by Paola Bargagna‐Mohan et al., https://doi.org/10.1002/jnr.24757 .